A 10-year trend in cannabis potency (2013–2022) in different geographical regions of the United States of America - ElSohly, Mahmoud A.; Majumdar, Chandrani G.; Chandra, Suman; Radwan, Mohammed M. (Frontiers in Public Health, 2024)
Background The prevalence of cannabis as the most commonly used illicit substance in the United States and around the globe is well-documented. Studies have highlighted a noticeable uptrend in the potency of cannabis in the United states. This report examines the concentration of cannabinoids in illicit cannabis samples seized by the United States Drug Enforcement Administration (DEA) over the last 10 years (2013–2022). Methods Samples received during the course of study (2013–2022) were categorized based on the geographical region where collected, as Western Region, Midwest Region, Northeast Region, South East Region, Southern Region as well as Alaska and Hawaii. These samples were processed for analysis using a validated gas chromatography with flame ionization detector method. Results The data showed that the cannabinoids profile of all high Δ9-THC cannabis samples, regardless of the state or region from which the samples are seized or the state from which the sample is produced under a state medical marijuana program, is basically the same with the major cannabinoid being Δ9-THC (>10% for most samples) and all other cannabinoids with less than 0.5%, with the exception of CBG (<1%) and CBN (<1%). Conclusion Overall, it appears the cannabinoids profile is controlled by the genetics of the plant and is not affected much by the geographical location in which the plants are cultivated.